Institutional arrangements for land drainage in developing countries - Freisem, C.; Scheumann, W. (International Water Management Institute, 2001)
The literature review on "Institutional arrangements for land drainage in developing countries" provides an overview over irrigation and drainage development, drainage problems and, in particular, displays the institutional arrangements in selected countries (Egypt, India, Peru, the Philippines and South Africa). India, the Philippines and South Africa are countries where IWMI is interested in carrying out research on the relationship between the effectiveness of institutions and performance; Egypt has developed institutions capable of addressing drainage needs; Peru is in the process of establishing Autonomous Hydrological Basin Authorities for catchment-wide management of water resources including drainage.